ANALISIS PRODUKTIVITAS KELOMPOK WANITA TANI (KWT) DI KABUPATEN KLUNGKUNG - Pratama, Pande Putu Ade Ananda; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Currently, a number of Women Farmers Groups (KWT) in Klungkung Regency have long developed the Sustainable Food Garden (P2L) program. The P2L program was initiated by the central government. Since its launch, Klungkung Regency now has 6 KWTs developing the program. The objectives to be achieved in this study are: 1) to analyze the direct influence of the variables of education, age, and number of dependent children on the working hours of the Women Farmers Group in Klungkung Regency; 2) analyze the direct effect of education, age, number of dependent children and working hours on the productivity of the Women Farmers Group in Klungkung Regency; and 3) analyzing the indirect effect of education, age, number of dependent children on productivity through the working hours of the Women Farmers Group in Klungkung Regency. The sampling technique used is proportional random sampling. The analytical technique used in this research is Path Analysis. The results of this study are: 1) education, age, and number of dependent children have a positive effect on the outpouring of working hours for women farmers groups in Klungkung Regency; 2) age and number of dependents have no effect, while education and working hours have a positive effect on the productivity of women's farmer groups in Klungkung Regency; and 3) working hours as an intervening variable the effect of education, age and number of dependent children on the productivity of women farmers groups in Klungkung Regency. The implication of this research is that increasing education, age, and number of dependents will increase working hours, and increasing education and hours will increase productivity, while age and number of dependents have no significant effect on KWT productivity in Klungkung Regency. Working hours as an intervening variable. Keywords: Women Farmers Group, education, age, number of dependent children, working hours, productivity